Bagaimana Keterlibatan Kerja, Perilaku Kerja Inovasi, dan Lingkungan Kerja Fisik Menjelaskan Kinerja Karyawan Vosco Group? - Rr. Levana Bonadea Ajiardani; Widiya Dewi Anjaningrum (Jurnal Ecogen, 2022)
The corona virus outbreak has an impact on decreasing income for culinary business. Knowing and analyzing the mediating role of innovation work behaior on the effect of work engagement and physical work environment on the performance of all Vosco Group employees is the main objective of this study. A total of 37 respondents have filled out the questionnaire without exception, employees from the Vosco Group culinary business: Vosco Coffee Malang, Vosco Coffee Heritage, Fry N Shake by Vosco Coffee, and Kim Jong Yum Korean BBQ. The quantitative data was finally analyzed in depth through PLS-analysis with SmartPLS-3.3.5 software. The results are quite surprising because all hypotheses are accepted and it is proven that innovation work behavior has an important role as a mediator of the effect of work engagement and physical work environment on employee performance. Further research is recommended to review and differentiate each café and to examine how to grow innovation work behavior in passive employees.